2015
DOI: 10.1038/eye.2014.320
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field imaging and OCT vs clinical evaluation of patients referred from diabetic retinopathy screening

Abstract: PurposeCompare wide-field Optomap imaging and optical coherence tomography (OCT) with clinical examination in diabetic retinopathy (DR).MethodsPatients referred from Diabetic Eye Screening Programmes to three centres underwent dilated ophthalmoscopy and were assigned a DR grade. Wide-field colour imaging and OCT were then examined by the same clinician at that visit and a combined grade was assigned. Independent graders later reviewed the images and assigned an imaging-only grade. These three grades (clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 21 publications
(29 reference statements)
0
42
0
1
Order By: Relevance
“…Other studies have tested and modified screening protocols using nonmydriatic imaging, single-field imaging and automated detection systems with variable results [3,4,20,21,22]. A recent study using wide-field imaging and OCT showed improvements in the detection rates of higher grades of diabetic retinopathy compared to clinical examination [23]. From the ophthalmologist perspective, an advantage of the multicolor imaging on the combined cSLO + SD-OCT platform is that a single device can perform all imaging modalities required.…”
Section: Clinical Applications Of Multicolor Imagingmentioning
confidence: 99%
“…Other studies have tested and modified screening protocols using nonmydriatic imaging, single-field imaging and automated detection systems with variable results [3,4,20,21,22]. A recent study using wide-field imaging and OCT showed improvements in the detection rates of higher grades of diabetic retinopathy compared to clinical examination [23]. From the ophthalmologist perspective, an advantage of the multicolor imaging on the combined cSLO + SD-OCT platform is that a single device can perform all imaging modalities required.…”
Section: Clinical Applications Of Multicolor Imagingmentioning
confidence: 99%
“…6 New technologies, such as wide-field imaging and OCT, being introduced routinely into HES, are improving accuracy of diagnoses. 7 Wide-field imaging detects more new vessels in more patients than the standard two 45°images used by the DESP. 8 These differences in diagnosis continue to challenge both graders and ophthalmologists, but can be resolved with a better understanding of the processes in each service and with better communication between them.…”
Section: Discussionmentioning
confidence: 99%
“…9 One study showed that Optomap imaging enabled earlier diagnosis of higher grades of diabetic retinopathy compared with clinicians performing slit lamp biomicroscopy of the fundus. 10 Similarly, wide-field imaging has been shown to capture more retinal nonperfusion, neovascularization, and panretinal photocoagulation than the seven-standard fields obtained by the ETDRS protocol (see Figure 3). Wessel et al reviewed 236 Optos…”
Section: Diabetic Retinopathymentioning
confidence: 99%